EFEKTIVITAS AROMATERAPI MELATI TERHADAP PENURUNAN KECEMASAN IBU POSTPARTUM - Ni Made Ari Febriyanti; Ni Ketut Ayu Sugiartini; Ni Wayan Sukma Adnyani; Ni Made Rai Widiastuti (LPPM Universitas Abdurrab, 2025)
The postpartum period is the period that begins after the baby is born until the woman's organs recover to their pre-natal state. During this period, women experience various adaptations, both physiologically, psychologically, and socially. One of the common psychological problems experienced by mothers after giving birth is anxiety. One way to reduce this anxiety is to use jasmine aromatherapy. This study aims to evaluate the effectiveness of jasmine aromatherapy in reducing anxiety levels in postpartum mothers. The research design used was a quasi-experiment with a one group pretest-posttest design without control, which was carried out in the work area of ​​Puskesmas I, East Denpasar. The number of samples taken was 30 respondents who met the inclusion criteria. The sampling method used in this study was purposive sampling. The independent variable in this study was jasmine aromatherapy, while the dependent variable studied was a decrease in anxiety levels. Data were collected using an anxiety level questionnaire using the Zung Self Rating Anxiety Scale (ZSAS) and data analysis was carried out in stages including univariate and bivariate (paired T-test). Based on the results of the study, almost half (40%) of respondents had mild anxiety before being given jasmine aromatherapy and almost all (86.7%) of respondents did not have anxiety after being given jasmine aromatherapy. Bivariate results showed a significant effect of reducing postpartum maternal anxiety before and after being given jasmine aromatherapy (p value 0.000). It is expected that health workers can use jasmine aromatherapy on postpartum mothers as an alternative to reduce anxiety and discomfort.